2015
DOI: 10.1200/jgo.2015.000125
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Palliative Care Into Comprehensive Cancer Treatment at Moi Teaching and Referral Hospital in Western Kenya

Abstract: PurposeThe prognosis for the majority of patients with cancer in Kenya is poor, with most patients presenting with advanced disease. In addition, many patients are unable to afford the optimal therapies required. Therefore, palliative care is an essential part of comprehensive cancer care. This study reviews the implementation of a palliative care service based at the Moi Teaching and Referral Hospital in Eldoret, Kenya, and describes the current scope and challenges of providing palliative care services in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…While such integration should be informed by recent international consensus regarding palliative integration, 37 it must also account for potential obstacles unique to resource-limited settings. 16,38 Specific and locally relevant parameters are needed to guide early collaboration with palliative specialists and to help oncologists decide whom to refer.…”
Section: Discussionmentioning
confidence: 99%
“…While such integration should be informed by recent international consensus regarding palliative integration, 37 it must also account for potential obstacles unique to resource-limited settings. 16,38 Specific and locally relevant parameters are needed to guide early collaboration with palliative specialists and to help oncologists decide whom to refer.…”
Section: Discussionmentioning
confidence: 99%
“…This was facilitated using referrals and members from the PC team attending ward rounds or offering consultations on symptom management. ‘Outpatient clinics’: many interventions used this mechanism to integrate PC into a facility, ( Molyneux et al , 2013 ; DesRosiers et al , 2014 ; Cornetta et al , 2015 ; Lowther et al , 2015 ; Zipporah, 2016 ; Gwyther et al , 2018 ). Usually individuals were seen together with their caregiver; however group outpatient clinics were also described ( DesRosiers et al , 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…These were often home visits ( Herce et al , 2014 ), according to set criteria, such as those whose mobility is heavily effected ( Hongoro and Dinat, 2011 ) and children whose caregivers could not carry them in ( Amery et al , 2009 ), and also found in the form of mobile clinics ( Herce et al , 2014 ), visits to other facilities, such as children homes ( Amery et al , 2009 ) and other health centres ( Tapsfield and Bates, 2011 ). ‘Telephonic advisory service’: telephonic consultations were used to manage patients’ symptoms at home ( Hongoro and Dinat, 2011 ; Cornetta et al , 2015 ) and to provide follow-up and bereavement calls ( Gwyther et al , 2018 ). ‘Treatment plans’: specialist PC teams often developed care plans that would be used while the patient is in the facility and following discharge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations